A Blockchain-Assisted Lightweight Anonymous Authentication Scheme for Medical Services in Internet of Medical Things - Wu, Shu; Zhang, Aiqing; Chen, Jindou; Peng, Guangyu; Gao, Ya (Wireless personal communications, 2023)
Internet of medical things (IoMT) enable physicians to provide precise care on the Internet for registered patients anywhere, bringing convenience to people’s everyday life. Considering the importance of patient’s privacy in IoMT, data security between patients and medical servers should be protected. Therefore, the authentication of identity and the agreement of a shared secret key are particularly important. In this work, we propose a lightweight anonymous authentication scheme between patients and medical servers in IoMT. We combine blockchain technology with biometric technology in order to form a shared session secret key. It can protect the privacy of patients through mutual authentication between patients and servers. Afterwards, the formal analysis of BAN logic shows that our scheme is secure. Non-formal analysis shows that our scheme achieves designed security objectives. Finally, comprehensive comparative experiments show that our proposed scheme achieves a better performance in both computation and communication efficiency.